Cosmopolitan Habits: The Capacities and Habitats of Intercultural Conviviality. (June 2013) - Noble, Greg
Public debate around cultural diversity has been dominated by a focus on 'panicked multiculturalism' – those spaces which have been subject to social anxieties because of perceived conflicts around ethnicity. This article attempts to address the habitual ways cultural differences are transacted and reconciled in the daily conduct of people in culturally diverse settings. Although habit has been a central category for understanding racial prejudice, it has rarely impacted on an understanding of the practices and capacities which people develop for living with difference, the routinised 'civic virtues' of intercultural life. Cosmopolitanism and conviviality have become significant tools in framing this enquiry, though not without problems. The issue for this article is whether these terms are methodologically useful for the analysis of the habits of 'civic virtues'. This article, drawing on the everyday interactions in and around a school, argues that we need to conceptualise conviviality as an object of empirical research. This requires that we think about habit as a pedagogical process, and the temporal and spatial elements through which 'cosmopolitan' behaviours are habituated.